Upaya Mengatasi Bullying Serta Apa Peran Guru Dalam Perilaku Bullying Di Sekolah Dasar (SD) - Nuri Laily fajriyanti; Safika Aisyah Putri (JURNAL ILMIAH RESEARCH STUDENT, 2025)
The purpose of this article is to find out that this Bullying behavior is very dangerous, and should not be normalized. This article was also created to find out how to overcome Bullying and what the role of teachers is in Bullying behavior in elementary schools. When there was news of Bullying against elementary school students which resulted in death, almost everyone was shocked and blamed each other. The world of education is being sued by both the Ministry of Education, schools and teachers who teach. Parents are also questioned about their role in educating children. Bullying is a form of aggressive, violent action that hurts other people continuously The causes are varied, starting from a family environment that is always fighting, shows that are less educational, a social environment that is less friendly and even teachers who still don't fully understand how to deal with Bullying behavior at school. The method we use in this article is qualitative research (literature study or literature review) with various written sources available through reading journals, scientific articles, books and relevant reports.